Analysis of Customer Relationship Management in The Business to Business Segment at The Titan Division of PT. Novell Pharmaceutical Laboratories - Jajang Suherman; Rasyid Shidiq Shidiq; A. Supriadi Adung Adung (Jurnal Maps (Manajemen Perbankan Syariah), 2026)
PT. Novell Pharmaceutical Laboratories is one of the national pharmaceutical companies that produces various types of medicines. To support its presence in the market, the company has several distribution branches, one of which is the Titan Division. In carrying out its duties, the Titan Division interacts directly with various professional parties in the health sector through a B2B approach, namely with hospitals. The presence of Customer Relationship Management (CRM) in the Titan Division becomes an important instrument in efforts to build more personal relationships and ensure product information can be conveyed accurately. The problem that occurred in the Titan Division is the lack of transparency in the reporting of prescription creation made by doctors, such as a scenario where a doctor has already made a prescription for a certain product, but the report that comes in is instead redirected to another user. Therefore, there is a need for neat digital record-keeping. The purpose of this research is to provide an overview of the strategies and impacts of CRM implementation on companies and related institutions. The research methods used in this study consist of several steps, namely a literature review, conducted by searching for supporting literature that can provide adequate information to complete this research and help reinforce existing theories. The implementation of CRM in the Titan Division provides tangible benefits, not only serving as an administrative tool but also in building closer relationships with business partners in the healthcare sector. From the research results, it can be concluded that CRM plays a significant role in increasing sales, strengthening partner trust, and creating loyal customers, thus becoming a long-term asset for the company.